Transition Metal Complexes of a Salen–Fullerene Diad: Redox and Catalytically Active Nanostructures for Delivery of Metals in Nanotubes. Issue 36 (23rd July 2013) - Lebedeva, Maria A.; Chamberlain, Thomas W.; Davies, E. Stephen; Mancel, Dorothée; Thomas, Bradley E.; Suyetin, Mikhail; Bichoutskaia, Elena; Schröder, Martin; Khlobystov, Andrei N.
Abstract A covalently‐linked salen–C60 (H2L) assembly binds a range of transition metal cations in close proximity to the fullerene cage to give complexes [M(L)] (M=Mn, Co, Ni, Cu, Zn, Pd), [MCl(L)] (M=Cr, Fe) and [V(O)L]. Attaching salen covalently to the C60 cage only marginally slows down metal binding at the salen functionality compared to metal binding to free salen. Coordination of metal cations to salen–C60 introduces to these fullerene derivatives strong absorption bands across the visible spectrum from 400 to 630 nm, the optical features of which are controlled by the nature of the transition metal. The redox properties of the metal–salen–C60 complexes are determined both by the fullerene and by the nature of the transition metal, enabling the generation of a wide range of fullerene‐containing charged species, some of which possess two or more unpaired electrons. The presence of the fullerene cage enhances the affinity of these complexes for carbon nanostructures, such as single‐, double‐ and multiwalled carbon nanotubes and graphitised carbon nanofibres, without detrimental effects on the catalytic activity of the metal centre, as demonstrated in styrene oxidation catalysed by [Cu(L)]. This approach shows promise for applications of salen–C60 complexes in heterogeneous catalysis.